2018
DOI: 10.4028/www.scientific.net/nhc.19.34
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Nickel and Boron Co-Substituted NaCo<sub>2</sub>O<sub>4</sub> Prepared by Electrospinning Technique

Abstract: In this study nickel and boron doped sodium cobalt oxide NaCo2-xNixByO4 (0≤x≤0.3, 0≤y≤0.1) nanocrystalline thermoelectric ceramic powders were synthesized using electrospinning techniques and then consolidated into bulk ceramics. The differences in the microstructure and thermoelectric properties of the samples as a result of doping effect have been investigated. The crystalline structures of the powders and nanofibers were characterized using X-ray diffraction and scanning electron microscopy and BET Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For industrial applications and competitive energy conversion ZT $ 1 is considered to be a desirable benchmark. 21,22 Figures of ZT > 1 have already been reported for p-type oxides; 23,24 however, for n-type oxides, ZT barely exceeds 0.5, 25 and this value has only been measured in ZnO ceramics at very high temperatures (T > 1000 K). 26 For STO-based materials, the highest experimental ZT reported to date is 0.46 at T ¼ 1000 K, which was measured in a Pr (5%):Nb (20%)-doped STO superlattice.…”
Section: Introductionmentioning
confidence: 94%
“…For industrial applications and competitive energy conversion ZT $ 1 is considered to be a desirable benchmark. 21,22 Figures of ZT > 1 have already been reported for p-type oxides; 23,24 however, for n-type oxides, ZT barely exceeds 0.5, 25 and this value has only been measured in ZnO ceramics at very high temperatures (T > 1000 K). 26 For STO-based materials, the highest experimental ZT reported to date is 0.46 at T ¼ 1000 K, which was measured in a Pr (5%):Nb (20%)-doped STO superlattice.…”
Section: Introductionmentioning
confidence: 94%
“…It has been found that the mechanical stretching in the electro‐spinning process is more effective than applied electrical polarization to induce ferroelectric phases . In addition, the advantage of this method over other methods, is making the material more homogeneous, robust and easily preparable .…”
Section: Introductionmentioning
confidence: 99%
“…Given the phenomenal and promising low κ L in Na 1−x CoO 2 , doping has extensively been used to improve the Seebeck coefficient of Na 1−x CoO 2 further with the ambition of bringing its ZT to values above unity [7,8,21,[23][24][25][26][27][28][29][30][31][32]. Nonetheless, dopants have usually been chosen based on the mere nominal oxidation state, atomic mass considerations and the solubility limits of the applied synthesis method [33].…”
Section: Introductionmentioning
confidence: 99%